STUDY REGARDING THE OCCURRENCE OF LATERALITY DISTURBANCES IN PRIMARY SCHOOL CHILDREN. INTERVENTION MEASURES - Alina Mihaela CRISTUŢĂ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Throughout life, on his way to evolution and development, man experiences different stages of his growth through the appearance of new skills and physical and psychic transformations. At the level of primary school, there appear and manifest quite an important number of preferences and transformations of the child on his way to development. These are due to the processes of attending school, learning new skills, experimenting different activities or revealing already present preferences. The aim of this research is to find, correct and educate laterality disturbances in primary school children. For a better organization of the study, the following hypotheses have been set: presumably, by applying specific tests one can see the incidence of laterality disturbances in primary school children and establish a lateral dominant; presumably, by implementing specific intervention measures one can correct the laterality disturbances in this group of subjects. The objectives we have followed in this research were those of gathering data and information necessary to the process of educating laterality disturbances, of offering solutions for the correction of these disturbances through specific exercises and of comparing the results of initial tests with those of the final tests in order to verify the efficiency of the corrective intervention programmes throughout the entire activity of research. The research methods were established according to the objectives of the research, as follows: the study of the professional literature method, the testing method, the statistical-mathematical method and the graphical representation method. At the end of the research, it can be concluded that this study regarding the occurrence of laterality disturbances in children from primary school contributed to: the discovery of laterality disturbances and the establishing of the type of laterality; additionally, the main results of the intervention measures are the development and the consolidation of motor skills, but also the stabilization and finalization of the lateral dominant and the raising of the subjects' awareness in what the lateral dominant is concerned.